Brain metastases associated with germ cell tumors may be treated with chemotherapy alone. Issue 11 (25th March 2014) - Hardt, Anna; Krell, Jonathan; Wilson, Peter D.; Harding, Victoria; Chowdhury, Simon; Mazhar, Danish; Berney, Dan; Stebbing, Justin; Shamash, Jonathan
Abstract : BACKGROUND: The management of brain metastases in patients with germ cell tumors remains controversial. The authors assessed the outcome in this patient group after the introduction of GAMEC chemotherapy (14‐day cisplatin, high‐dose methotrexate, etoposide, and actinomycin‐D with filgrastim support) and cessation of the routine use of cranial irradiation. METHODS: Data were recorded prospectively from 39 patients with germ cell tumors and concurrent brain metastases who received treatment before and after the advent of GAMEC after they relapsed on conventional cisplatin‐based chemotherapy. Neurosurgery was offered to selected patients. Radiotherapy generally was used only as a salvage therapy after chemotherapy failure. The primary outcome measure was overall survival and was depicted using a Kaplan‐Meier plot. RESULTS: The 3‐year overall survival rates were 38% for the whole cohort, 69% for those who presented with brain metastases at diagnosis (group 1), and 21% and 0% for those who developed metastases after initial chemotherapy (group 2) and while receiving chemotherapy (group 3), respectively. For the whole cohort, the median overall survival was 10.6 months (range, 5.5 months to not evaluable); and, for groups 1, 2, and 3 individually, the overall survival was not yet reached (range, from 7.4 months to not evaluable), 6.2 months (range, 2.1‐15.3 months), and 2.7 months (range, from 0.6 months to not evaluable), respectively. The 3‐year survival rate for those who received GAMEC chemotherapy was 56% compared with 27% for those who received chemotherapy pre‐GAMEC. CONCLUSIONS: The prognosis for patients with germ cell tumors and brain metastases seems less bleak than previously thought. It is possible to achieve long‐term survival with chemotherapy alone. Cancer 2014;120:1639–1646 . © 2014 American Cancer Society . Abstract : Current data from a single‐institution study of patients with advanced testicular germ cell tumors and brain metastases suggest that GAMEC chemotherapy (14‐day cisplatin, high‐dose methotrexate, etoposide, and actinomycin‐D with filgrastim support) can achieve long‐term survival on its own, without the need for additional treatment modalities.